Assessment of effect of educational intervention on awareness, attitude, and practice regarding pharmacovigilance practices among patients admitted in a tertiary healthcare center in South India - Vishvas, Ananya; Harindran, Pratheeksha; Nanjundappa, Shiva Murthy (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Adverse drug reactions (ADRs) remain a significant contributor to global morbidity and mortality. Despite the launch of the Pharmacovigilance Programme of India (PvPI) to improve ADR reporting, under-reporting persists largely due to limited public awareness. Active consumer participation is essential for the success of pharmacovigilance systems. Objective of the study was to assess the impact of an educational intervention on the knowledge, attitude, and practice (KAP) regarding pharmacovigilance among inpatients at a rural tertiary healthcare center in South India. Methods: A prospective crossover study was conducted using a pre-validated KAP questionnaire. Adult inpatients aged 18–75 years, excluding healthcare workers, were enrolled via convenient sampling. An educational session tailored for non-medical individuals was delivered, followed by re-administration of the same KAP tool to assess changes. The target sample size was 175, with an additional 5 participants enrolled within the study period. Ethical approval and informed consent were obtained. Results: The study included 180 participants (96 males, 84 females) with a mean age of 40.15±15.30 years. Post-intervention, awareness of what constitutes an ADR rose markedly from 27.8% to 97.8%, and belief in the universal possibility of side effects increased from 20% to 98.9%. Willingness to report ADRs in the future improved slightly from 95% to 96.1%, although actual reporting practice remained limited. Overall, the educational session significantly enhanced participant awareness, attitudes, and understanding related to pharmacovigilance. Conclusions: Structured educational interventions can substantially improve public engagement in pharmacovigilance. Strengthening patient awareness and involvement, particularly in rural settings, is vital to advancing drug safety monitoring in India.